O estudo da PDE7 como novo alvo terapêutico em potencial no câncer de ovário - Tessarollo, Nayara Gusmão (2017)
Ovarian cancer (OC) is the leading cause of death among gynecological tumors. Despite significant advances in this kind of tumor research, the treatment still faces significant challenges, including chemoresistance. Among the potential targets in the treatment of CAOV, highlight the phosphodiesterase 7-A (PDE7-A). This enzyme degrades the cyclic adenosine monophosphate (cAMP) to adenosine monophosphate. In this context, this project aims to investigate the role of PDE7 and its mechanism of action in ovarian carcinoma. Previous data from RNA-seq showed higher expression of PDE7-A enzyme in ovarian serous carcinoma compared to the fallopian tube. Considering what has been said, metabolic cell viability assays (MCV) were conducted in two CAOV cell lines, A2780 and OVCAR3, using the selective PDE7 isoform inhibitor, designate BRL50481, in monotherapy and in combination with cisplatin (CISP) and paclitaxel (PTX). Our results showed that the use of the BRL50481 inhibitor in monotherapy reduced the A2780 cells MCV by about 60% in a dose-dependent manner in the 48 hour treatment. Although the treatment with BRL50481 in monotherapy in OVCAR3 cell line did not change the MCV, its association with CISP in 48 hour-treated cell, promoted a reduction of MCV. On the other hand, the association of BRL50481 and PTX promoted inhibition of MCV in both cell lines analyzed. An increase in the potency of PTX was also observed, an aspect verified with the reduction of the IC50 of PTX in relation to monotherapy. The treatment chronology in cell survival was also verified. Thus, pretreatment of A2780 with 200 μM BRL50481 followed by the associated treatment of BRL50481 and PTX promoted a reduction in MCV of around 70% compared to the treatment with PTX alone. For OVCAR3, 400 μM pretreatment of BRL 50481 provided a VCM reduction of about 20%. Therefore, our data showed beneficial effect between the PDE7 inhibitor and PTX, which allowed a reduction of the PTX concentration used in A2780 and OVCAR3 by about 82.7x108 and 80.4x103 times, respectively. Moreover, the possible mechanisms of action involved in the inhibition of PDE7 have been investigated. It has been observed that the PDE7 inhibition does not affect cell cycle progression. Furthermore, the combination of BRL50481 and PTX promoted increased cell necrosis in OVCAR3. In addition, pretreatment of the OVCAR3 with BRL50481 modulated the gene expression of the cytokines IL-6, IL-1α and IL-1β, as well as increased IL-6 secretion. The combination of BRL50481 and PTX further modulated negatively the PI3K / AKT / mTOR cell signaling pathway in both cell lines studied. In addition, the A2780 pre-treated cells showed an increase in the expression of the pro-apoptotic Bax protein. Still, cell death may be related to the induction of autophagy in the two study models. It has also been observed that CLDN-16 expression is modulated by the PKC, PI3K/AKT and PKA pathways and, by inhibiting PDE7, a greater expression of CLDN-16 was verified. Immunohistochemical analyzes revealed that 80% of the analyzed cases overexpress this protein. Interestingly, this is an anomalous expression, since in all the cases that showed expression of CLDN-16, it was restricted to the cytoplasm of the cells. These studies contributed to a better understanding of the mechanisms involved in the cellular proliferation of CAOV, allowing the exploration of new therapeutic strategies.